Penerapan Model Pembelajaran Kontekstual dalam Mata Pelajaran Akidah Ahlak pada Peserta Didik di MIN 1 dan MIN 2 Nganjuk - Nafhan Taufikul Khakim; Ali Imron; Sri Susanti Tjahja Dini (Intellektika : Jurnal Ilmiah Mahasiswa, 2025)
Contextual learning is a learning approach that helps teachers connect what they teach to students' real-world situations and encourages students to make connections between their knowledge and its application in everyday life. This research aims to explore the application of the contextual learning model in the Aqidah Ahlak subject for students at MIN 1 and MIN 2 Nganjuk. The research method used is qualitative with a case study approach. Data was collected through observation, interviews and document analysis. The research results show that the application of the contextual learning model helps increase the understanding and application of moral values ​​among students. The implication of this research is the need to integrate contextual learning models in the teaching of Aqidah Ahlak subjects at MIN 1 and MIN 2 Nganjuk.